2019
DOI: 10.1016/j.jtcme.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of α-amylase, lipase inhibition and in-vivo pharmacological activities of Eucalyptus camaladulensis Dehnh leaf extract

Abstract: In this present study, phytochemical screening, anti-ulcer assay, anti-diarrhea assay, anti-inflammatory assay, analgesic assay, lipase activity assay, amylase activity assay and the anti-bacterial activity of Eucalyptus camaladulensis Dehnh leaf extracted with methanol and 50% ethanol was analyzed for biological significance. Physical characterization of the non-volatile component revealed the higher yield of 16.92% in 50% ethanol expediting the use of 50% ethanol as a better alternativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Ten-gram powder of each sample was macerated with 100 mL of absolute methanol (HPLC-grade) and kept overnight on a rotary shaker (JEIO TECH, South Korea) at 150 rpm at 25°C temperature. On the next day, the entire mixture was filtrated and concentrated to dryness by evaporating on a vacuum evaporator (hanil Modul 4080C, South Korea) as the slightly modified procedure of previous investigators [37]. The extracted crude samples were kept in airtight glass vials and stored at 4°C until use.…”
Section: Plant Collection Authorization and Extract Preparationmentioning
confidence: 99%
“…Ten-gram powder of each sample was macerated with 100 mL of absolute methanol (HPLC-grade) and kept overnight on a rotary shaker (JEIO TECH, South Korea) at 150 rpm at 25°C temperature. On the next day, the entire mixture was filtrated and concentrated to dryness by evaporating on a vacuum evaporator (hanil Modul 4080C, South Korea) as the slightly modified procedure of previous investigators [37]. The extracted crude samples were kept in airtight glass vials and stored at 4°C until use.…”
Section: Plant Collection Authorization and Extract Preparationmentioning
confidence: 99%
“…Previous research studies have shown that medicinal plants exhibited pronounced inhibitory effects towards the activities of a-amylase, lipase and inflammation (Kang et al, 2015;Ghasemian et al, 2016;Von Dentz, et al, 2020;Joshi et al, 2018;Feng et al, 2020;Mohamed et al, 2020;Tiss et al, 2020). In fact, Plants are a source of bioactive secondary metabolites such as glycosides, saponins, flavonoids, steroids, tannins, alkaloids and terpenes, which act as strong antioxidant to protect body from oxidative damage (Upreti et al, 2019). These secondary metabolites have shown several biological activities such as antibacterial, antioxidant, anti-inflammatory, antiulcer, analgesic and also used for the treatment of diabetes (Upreti et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes one of the most challenging chronic disorder of the 21st century that alters carbohydrate, protein, and fat metabolisms. It is characterized by chronic hyperglycemia, caused abnormal insulin secretion or insulin action or both [12]. In fact, The rate of carbohydrate and lipid digestion can in uence or adversely affect postprandial glycaemia, weight gain, and obesity, particularly in people at risk of T2D.…”
Section: Discussionmentioning
confidence: 99%
“…At present, many treatments involving the use of medicinal plants have been recommended, since most contain compounds with antidiabetic, anti-in ammatory, anti-pyretic and analgesic effects and with low indices of toxicity [5,10,11]. Plants are huge source of bioactive secondary metabolites such as glycosides, saponins, avonoids, steroids, tannins, alkaloids and terpenes, which act as strong antioxidant to protect body from oxidative damage [12]. These secondary metabolites have shown several biological activities such as antibacterial, antioxidant, anti-in ammatory, antiulcer, analgesic and also used for the treatment of diabetes [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation